Sample-specific odontometric sex estimation: A method with potential application to burned remains. Issue 4 (July 2017) - Gouveia, Marcia Filipa; Oliveira Santos, Inês; Santos, Ana Luísa; Gonçalves, David
Abstract: Metric features are often the only preserved sexually dimorphic features to allow sex estimation in burned human remains, but this is complicated by heat-induced dimensional changes. The potential of odontometry for sex estimation was investigated. A sample of permanent lower second pre-molars from 20 males and 20 females was experimentally burned at 900 °C to assess heat-induced changes in the sexual dimorphism of seven dimensions of the cementum-enamel junction and the root. Four of them, cementum-enamel junction perimeter; mesiodistal, buccolingual and perimeter at the mid-root level, were investigated for the first time. Also, five measurements combining some of the isolated standard measurements were investigated. Additionally, 10 permanent upper central incisors and 10 permanent lower first molars were experimentally burned at 400 °C and 700 ° C to document heat-induced dimensional changes and serve as comparison with the 900 °C sample. Results showed that most of the standard measurements, although presenting significant sex differences, were not reliable enough to allow for correct sex classifications close to 100% both before and after the burning. Nonetheless, the perimeter at the cementum-enamel junction and the combined measurements of the mesiodistal and buccolingual diameters, at the same level, were quite promising in the post-burning analysis with correct sex classifications above 80%. At 900 °C, females were slightly more affected by shrinkage in this measure than males thus artificially increasing sexual dimorphism after burning. Therefore, and although additional research is needed, this feature was not discarded as having potential for skeletal sex estimation. Highlights: Metric sex estimation of burned skeletal remains is complicated by heat-induced changes. Dental roots are often preserved in fire scenarios and are a possible target for sex estimation. Potential of sample-specific sex estimation in experimentally burned teeth was investigated. Two out of 12 dental measurements provided successful sex classifications above 80%. Female teeth experienced more shrinkage than males artificially enlarging sex differences.